Symptoms networks in teachers suffering from burnout - Ana María Ruiz-Ruano García; Javier Rodríguez Fragoso; Enrique Javier Garcés de los Fayos Ruiz; Dyana Muñoz; Jorge López Puga; Francisco José Moya-Faz (Psychology, Society & Education)
Teacher psychological wellbeing is a key component to understand the educational system. The burnout is considered one of the most destructive disorders affecting teachers. In this research, a sample of 257 teachers (186 women, age ranging from 24 to 64 years, M = 42.58, SD = 9.8) was cluster analysed to find groups of teachers differing in burnout profiles. Symptoms networks (no directed and directed) for stress, depression, and anxiety were then estimated for each cluster. Results show that self-deprecation and devaluation of life are central symptoms of depression for teachers suffering from burnout. The subjective experience of anxiety is observed to be the central symptom for anxiety, whereas irritability/over-reactivity is the central symptom of stress in teachers suffering from burnout. Those results are useful to enhance our understanding of teaching burnout as well as to design interventions to minimize the negative impact of psychological symptoms in teachers. Intervention programs are suggested to be designed to prevent burnout in older teachers who show higher risk of suffering from occupational exhaustion. It is also suggested to increase the flows of compassion to reduce depression among those teachers scoring hight in burnout. Interventions based on cognitive behavioural therapy or mindfulness are proposed to be effective in those cases.